Evaluation of Therapeutic Efficacy and Safety of Tranexamic Acid Local Infiltration in Combination with Topical 4% Hydroquinone Cream Compared to Topical 4% Hydroquinone Cream Alone in Patients with Melasma: A Split-Face Study - Zohreh Tehranchinia; Bita Saghi; Hoda Rahimi (Dermatology Research and Practice)
Introduction. Melasma is an acquired pigmentary disorder characterized by hyperpigmented macules and/or patches affecting sun-exposed skin. Tranexamic acid (TA) can reduce melanin content of epidermis. Thus, we conducted this study to evaluate the efficacy and safety of tranexamic acid local infiltration in combination with topical 4% hydroquinone cream compared to topical 4% hydroquinone cream alone in patients with melasma. Material and Methods. This study was a prospective assessor- and analyst-blind, randomized split-face clinical trial which was performed on patients with bilateral malar epidermal melasma. A total of 55 patients were enrolled, and each side of their face was randomly allocated to either TA+HQ or HQ alone treatment. The MASI score was applied as an objective measurement to compare two treatment groups. The patient's satisfaction of melasma treatment was evaluated using a four-scale grading, as well. Results. The mean of MASI score in week 16 decreased in both groups significantly (p < 0.01). The therapeutic outcomes were significantly better in TA+HQ group than HQ group (p=0.001). Patients satisfaction with treatment was significantly higher in the TA + HQ group. The difference between the two groups regarding side effect occurrence was not statistically significant. Conclusion. Addition of tranexamic acid injections to conventional hydroquinone therapy can increase the efficacy of topical treatment. This trial is registered with IRCT2015110324865N1.